2019
DOI: 10.7554/elife.47088
|View full text |Cite
|
Sign up to set email alerts
|

Rapid decline of bacterial drug-resistance in an antibiotic-free environment through phenotypic reversion

Abstract: Antibiotic resistance typically induces a fitness cost that shapes the fate of antibiotic-resistant bacterial populations. However, the cost of resistance can be mitigated by compensatory mutations elsewhere in the genome, and therefore the loss of resistance may proceed too slowly to be of practical importance. We present our study on the efficacy and phenotypic impact of compensatory evolution in Escherichia coli strains carrying multiple resistance mutations. We have demonstrated that drug-resistance freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 56 publications
7
64
0
Order By: Relevance
“…The results from our various phenotypic assessments of BZKR and CETR growth and QAC tolerance phenotype stability ( Fig.1, Tables 2) also appear to agree with previous studies that show QAC adaptation generally comes at a fitness cost to the cell (39,40,60). In our growth curve experiments, we observed that QAC-adapted replicates all exhibited delayed growth when compared to WT (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…The results from our various phenotypic assessments of BZKR and CETR growth and QAC tolerance phenotype stability ( Fig.1, Tables 2) also appear to agree with previous studies that show QAC adaptation generally comes at a fitness cost to the cell (39,40,60). In our growth curve experiments, we observed that QAC-adapted replicates all exhibited delayed growth when compared to WT (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…Deletion of arcA significantly extended the time of appearance of colonies by 38% (t-test p-value < 1e-7) in the Tet R background but had little to no effect in the WT background ( Fig 3A). This result was reproduced in liquid cultures wherein fitness was measured as the Area Under the growth Curve [49][50][51] , demonstrating that the tetracycline resistance mutations had increased the importance of ArcA relative to its role in the WT background. Both lag phase and loss of fitness of the Tet R DarcA strain increased with tetracycline treatment at high doses (16 ug/ml-20 ug/ml) and the effects were completely reversed by complementation with an episomal copy of arcA ( Fig.…”
Section: Arca Activity Ameliorates the Fitness Cost Of Tetracycline Rmentioning
confidence: 83%
“…The AUC value integrates multiple properties of the growth curve 49 . For this reason and consistency among biological replicates 50 , it has been recently preferred over other fitness-related terms 50,51 . To evaluate fitness in solid LB medium (incubated at 37 o C), the time required to detect colonies in petri dishes (time of appearance) was determined using the ScanLag technology 48 for the analyzed strains.…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotic resistance mutations typically incur a fitness cost that favor sensitive strains in the absence of antibiotics. The phenotypic reversion to sensitive states is commonly caused by secondary mutations in other genes that alter resistance (37,38) or it could be caused by genotypic reversions in which the ancestral allele is selected under drug-free conditions (2,36,39). In our experimental system, assuming a conservative uniform distribution of mutation rate of 10 -3 /genome/generation (21), each base pair experiences approximately three mutations on average during the 12 days of serial transfers (21).…”
Section: Collateral Sensitivity Resulting From Genetic Reversionsmentioning
confidence: 99%